Shortened Lung Clearance Index is a repeatable and sensitive test in children and adults with cystic fibrosis. Issue 1 (22nd July 2014) - Hannon, David; Bradley, Judy M; Bradbury, Ian; Bell, Nicholas; Elborn, J Stuart; O'Neill, Katherine
Abstract : Background: Lung clearance index (LCI) derived from sulfur hexafluoride (SF6 ) multiple breath washout (MBW) is a sensitive measure of lung disease in people with cystic fibrosis (CF). However, it can be time-consuming, limiting its use clinically. Aim: To compare the repeatability, sensitivity and test duration of LCI derived from washout to 1/30th (LCI1/30 ), 1/20th (LCI1/20 ) and 1/10th (LCI1/10 ) to 'standard' LCI derived from washout to 1/40th initial concentration (LCI1/40 ). Methods: Triplicate MBW test results from 30 clinically stable people with CF and 30 healthy controls were analysed retrospectively. MBW tests were performed using 0.2% SF6 and a modified Innocor device. All LCI end points were calculated using SimpleWashout software. Repeatability was assessed using coefficient of variation (CV%). The proportion of people with CF with and without abnormal LCI and forced expiratory volume in 1 s (FEV1 ) % predicted was compared. Receiver operating characteristic (ROC) curve statistics were calculated. Test duration of all LCI end points was compared using paired t tests. Results: In people with CF, LCI1/40 CV% (p=0.16), LCI1/30 CV%, (p=0.53), LCI1/20 CV% (p=0.14) and LCI1/10 CV% (p=0.25) was not significantly different to controls. The sensitivity of LCI1/40, LCI1/30 and LCI1/20 to the presence of CF was equal (67%). The sensitivity of LCI1/10 and FEV1 % predicted was lower (53% and 47% respectively). Area under the ROC curve (95% CI) for LCI1/40, LCI1/30, LCI1/20, LCI1/10 and FEV1 % predicted was 0.89 (0.80 to 0.97), 0.87 (0.77 to 0.96), 0.87 (0.78 to 0.96), 0.83 (0.72 to 0.94) and 0.73 (0.60 to 0.86), respectively. Test duration of LCI1/30, LCI1/20 and LCI1/10 was significantly shorter compared with the test duration of LCI1/40 in people with CF (p<0.0001) equating to a 5%, 9% and 15% time saving, respectively. Conclusions: In this study, LCI1/20 was a repeatable and sensitive measure with equal diagnostic performance to LCI1/40 . LCI1/20 was shorter, potentially offering a more feasible research and clinical measure.